Novel Small-Molecule AMP-Activated Protein Kinase Allosteric Activator with Beneficial Effects in db/db Mice - Zhang, Li-Na (Public Library of Science, 2013)
AMP-activated protein kinase (AMPK) is an energy sensor of metabolism that is an attractive therapeutic target for type 2 diabetes mellitus and metabolic syndrome. Using a homogeneous scintillation proximity assay (SPA), we identified a new small-molecule AMPK activator, ZLN024, which allosterically stimulated active AMPK heterotrimers and the inactive α1 subunit truncations α1 (1–394) and α1 (1–335) but not α1 (1–312). AMPK activation by ZLN024 requires the pre-phosphorylation of Thr-172 by at least one upstream kinase and protects AMPK Thr-172 against dephosphorylation by PP2Cα. ZLN024 activated AMPK in L6 myotubes and stimulated glucose uptake and fatty acid oxidation without increasing the ADP/ATP ratio. ZLN024 also activated AMPK in primary hepatocytes, decreased fatty acid synthesis and glucose output. Treatment of db/db mice with 15 mg/kg/day ZLN024 improved glucose tolerance; liver tissue weight, triacylglycerol and the total cholesterol content were decreased. The hepatic transcriptional level of G6Pase, FAS and mtGPAT were reduced. The transcription of genes involved in fatty acid oxidation and the mitochondrial biogenesis of muscle tissue were elevated. The ACC phosphorylation was increased in muscle and liver. This study provides a novel allosteric AMPK activator for functional study in vitro and in vivo and demonstrates that AMPK allosteric activators could be a promising therapeutic approach for type 2 diabetes mellitus and metabolic syndrome.